Markedly Elevated Liver Enzymes in Choledocholithiasis in the absence of Hepatocellular Disease - Eula Plana Tetangco MD; Natasha Shah MD; Hafiz Muhammad Sharjeel Arshad MD; Hareth Raddawi MD (SAGE Publishing, 2016)
Liver enzyme levels are commonly obtained in the evaluation of many conditions. Elevated alanine transaminase and aspartate transaminase have traditionally been considered a "hepatocellular" pattern concerning for ischemic, viral, or toxic hepatitis. Elevations in these levels pose a diagnostic dilemma in patients without a clinical picture consistent with liver disease. On the other hand, elevated alkaline phosphatase historically represents a "cholestatic" pattern concerning for gallbladder and biliary tract disease. Often, patients present with a "mixed" picture of elevation in all 3 liver enzymes, further confounding the clinical scenario. We present 4 cases of women with severe upper abdominal pain and markedly elevated transaminases. Three of the patients had accompanying jaundice. A higher rise in enzyme levels was seen in those who had greater bile duct dilation. All patients saw a rapid decrease in transaminases after biliary decompression, along with a fall in alkaline phosphatase and total bilirubin levels. No evidence of liver disease was found, nor were there any signs of hepatocellular disease on imaging. The patients were ultimately found to have choledocholithiasis on endoscopic retrograde cholangiopancreatography with no hepatocellular disease. Furthermore, our cases show that severe abdominal pain in the setting of elevated liver enzymes is likely associated with biliary disease rather than a primary hepatic process. Recognition of this rare pattern of markedly elevated transaminases in isolated biliary disease can aid in avoiding unnecessary evaluation of primary hepatic disease and invasive surgical interventions such as liver biopsy.